Parenting Patterns In The Use Of Gadgets On The Social Emotional Development Of Preschool Children In Tk- Dharma Wanita Mangunrejo - Ida Arafah; Setyo Budi Susanto (Universitas STRADA Indonesia, 2023)
Parenting can be defined as a pattern of interaction between children and their parents which includes the fulfillment of physical needs (such as eating, drinking, etc.) and psychological needs (such as security, affection, etc.), as well as socialization of norms. prevailing in society so that children can live in harmony with their environment. This study aims to analyze the relationship of parenting in the use of gadgets to the social and emotional developmentof preschool children at Tk Dharma Wanita Mangunrejo. This type of research is quantitative with analytic correlation research design and the type of research used is cross sectional. This research was conducted at Tk Dharma Wanita Mangunrejo in August 2022. The population in this study were all parents of students who attended Tk-Dharma Wanita Mangunrejo with a total of 80 parents. By calculating using the solvin formula, the number of samples was 67 parents of students. The sampling technique used is simple random sampling technique. Collecting data using data using a questionnaire with chi-square test. The results showed that the analysis using the chi-square test had a significance of 0,000. Seeing that there is no expected count value that is less than 5 so that it meets the requirements of the chi-square test has a significance of 0,000 (<0,005) meaning that there is a relationship between parenting patterns in the use of gadgets on the social and emotional development of preschool children at Tk- Dharma Wanita Mangunrejo.